Northwest Semitic Vocabulary in Akkadian Texts - Huehnergard, John
Besprechungsartikel von D Sivan, Grammatical Analysis and Glossary of the Northwest Semitic Vocables in Akkadian Texts of the 15th-13th C. B.C. from Canaan and Syria (AOAT 214, 1984)